if1-i is a root, so its complex conjugate, 1+i. Write factors(x-k) where k is a root for all 3 roots. Then multiply together.

\((x-(-5))(x-(1-i))(x-(1+i))=(x+5)(x^{2}-x(1+i)-x(1-i)+1(1-i)(1+i))\)

\(=(x+5)(x^{2}-x-ix-x+ix+1ii^{2})\)

\(=(x+5)(x^{2}-2x+2)\)

\(=x^{3}-2x^{2}+2x+5x^{2}-10x+10\)

\(=x^{3}+3x^{2}-8x+10\)

\((x-(-5))(x-(1-i))(x-(1+i))=(x+5)(x^{2}-x(1+i)-x(1-i)+1(1-i)(1+i))\)

\(=(x+5)(x^{2}-x-ix-x+ix+1ii^{2})\)

\(=(x+5)(x^{2}-2x+2)\)

\(=x^{3}-2x^{2}+2x+5x^{2}-10x+10\)

\(=x^{3}+3x^{2}-8x+10\)